Biblioteca especializada e acesso à informação de interesse público - Silva, Merielem Frasson da (2023)
The State of Espírito Santo has several specialized libraries working in government agencies and companies. This study investigates the specialized libraries in the three powers of the State of Espírito Santo and their contribution to accessing information of public interest. Specifically, it maps existing specialized libraries; discusses the state of the art in Librarianship and Information Science; identifies the situational framework of specialized libraries; characterizes the role of these libraries and reflects on the library specialized in the management and access to information of public interest. The method used is exploratory-descriptive research with a qualitative and quantitative approach. In methodological procedures, it was instrumented with bibliographical, documental and field research. The bibliographical and documental survey was carried out in databases such as Illinois Digital Environment for Access to Learning and Scholarship, Reference Database of Journal Articles in Information and Information Science, among others, in addition to the preliminary study. In the field research, an online questionnaire was applied to professionals responsible for specialized libraries and institutions that do not have libraries. For data analysis, an information access maturity matrix was used. It concludes that the specialized library is suffering the impacts of the adopted informational policies, but persists and plays an important role in state government institutions.